2015
DOI: 10.1159/000441560
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Personalized Medicine in the Canadian Environment: Efforts Facilitating Oncology Clinical Research

Abstract: There is currently a rapid evolution of clinical practices based on the introduction of patient stratification and molecular diagnosis that is likely to improve health outcomes. Building on a strong research base, complemented by strong support from clinicians and health authorities, the oncology field is at the forefront of this evolution. Yet, clinical research is still facing many challenges that need to be addressed in order to conduct necessary studies and effectively translate medical breakthroughs based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…– Network of Centres of Excellence (academia, industry, government and non-profit organisations) [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…– Network of Centres of Excellence (academia, industry, government and non-profit organisations) [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…– Operationalisation and streamlining of research are made on a national level, while healthcare decisions are made within provincial boundaries [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It depends, also, on the level of discordance between research prioritization at national or international agenda. The latter, alongside with lack of harmonization of legal and ethical guidelines are considered by the experts as the main barriers to financing research in PM [ 17 , 18 ]. Healthcare systems have fragmented legislations and PM policies and programmes vary significantly among countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although public-private financing agreements (Polychronakos, 2012 ; Power et al, 2014 ) and performance-based reimbursement (De Souza et al, 2012 ) mechanisms were suggested as potential strategies (Koleva-Kolarova et al, 2022 ), the successful implementation of these strategies faced various issues. Among these, the disconnect between academic and private sectors (Gurwitz et al, 2009 ), the misalignment in research priorities nationally and internationally (Syme et al, 2015 ) as well as the ethical and legal issues surrounding data and sample sharing (Vis et al, 2017 ). Other issues revolve around generating outcome data and the inability to implement risk-sharing agreements across different healthcare systems, compounded with the health technology assessment frameworks, which are not fit to the uncertainty of precision oncology interventions (Regier et al, 2022 ).…”
Section: Scaling Clinical Implementation Requires Pragmatic Rationali...mentioning
confidence: 99%